Biological Reduction of Perchlorate from Spent Modified Reed Mediated by an Enriched Microbial Culture. (3rd February 2023) - Baidas, Salem; Al-Deyain, Khaled; Meng, Xiaoguang; Gao, Baoyu
Abstract : Disposal of untreated perchlorate-laden modified reed (MR) generated in the treatment of contaminated water risks further contamination issues. The primary aim of this study was to assess the enriched microbial culture (EMC)-mediated biodegradation of perchlorate bound to spent quaternary amine-MR adsorbent. The culture was enriched to utilize perchlorate as an electron acceptor and brewer's yeast as an electron donor. Kinetics experiments were performed to determine biodegradation rates and the total time for complete removal. The secondary aim of this research was the development and testing of a microwave-assisted extraction (MAE)-facilitated accurate perchlorate quantitation method. Extraction efficiency was optimized by adjusting the nitric acid concentration, resulting in 90 ± 5% recovery. Results show that EMC can degrade aqueous perchlorate effectively and consistently. EMC can also effectively degrade adsorbed perchlorate from spent MR. In conclusion, anaerobic biodegradation of perchlorate from spent MR can be used as an efficient, cost-effective, and environmentally friendly alternative or supplement to other treatment options, such as ion exchange and incineration. This approach can also be an effective solution to the waste generated by using MR to remove perchlorate from contaminated water.